Clinical Characteristics of Cognitive Subgroups of Obsessive Compulsive Disorder - Emre Mısır; Raşit Tükel; Berna Binnur Akdede; Emre Bora (Brain and Behavior)
ABSTRACT Introduction Obsessive‐compulsive disorder (OCD) is a clinically heterogeneous disorder. The results of symptom‐based classification studies are inconsistent in resolving this heterogeneity. The aim of this study was to investigate clinical differences between clusters created according to neurocognitive performance. Methods This study combined data sets from three previously published studies. A total of 135 outpatients diagnosed with OCD, and 106 healthy controls (HCs) were evaluated using the 17‐Item Hamilton Depression Rating Scale (HDRS‐17) and a comprehensive neuropsychological battery. Patients were also administered the Yale‐Brown Obsessive Compulsive Scale (Y‐BOCS). Results Two neurocognitive subgroups were identified by k‐means cluster analysis: globally impaired (GI, n = 42) and cognitively intact (CI, n = 93). The GI subgroup performed worse than the HC and CI groups on all neurocognitive tests. There was no difference between the CI group and HC in any cognitive domains. Compulsive symptom severity [t(133) = −2.45, p = 0.015], Y‐BOCS total score [t(133) = −2.09, p = 0.038], and age of onset were higher in the GI group than in the CI group [t(132) = −4.24, p < 0.001]. Years of education were higher in the CI and HC groups than in the GI group [F(238) = 35.27, p < 0.001]. There was no difference in symptom profile between the CI and GI groups. Conclusion The identified cognitive clusters may indicate subtypes with different neurobiological bases. A better dissection of the cognitive structure of OCD could potentially facilitate genetic and neuroimaging studies.